Distinct Occurrence of Proarrhythmic Afterdepolarizations in Atrial Versus Ventricular Cardiomyocytes: Implications for Translational Research on Atrial Arrhythmia - Bögeholz, Nils; Pauls, Paul; Dechering, Dirk G.; Frommeyer, Gerrit; Goldhaber, Joshua I.; Pott, Christian; Eckardt, Lars; Müller, Frank U.; Schulte, Jan S. (Frontiers in Pharmacology, 2018)
Background: Principal mechanisms of arrhythmia have been derived from ventricular but not atrial cardiomyocytes of animal models despite higher prevalence of atrial arrhythmia (e.g. atrial fibrillation). Due to significant ultrastructural and functional differences, a simple transfer of ventricular proneness towards arrhythmia to atrial arrhythmia is critical. The use of murine models in arrhythmia research is widespread, despite known translational limitations. We here directly compare atrial and ventricular mechanisms of arrhythmia to identify critical differences that should be considered in murine models for development of antiarrhythmic strategies for atrial arrhythmia. Methods / Results: Isolated murine atrial and ventricular myocytes were analyzed by wide field microscopy and subjected to a proarrhythmic protocol during patch-clamp experiments. As expected, the spindle shaped atrial myocytes showed decreased cell area and membrane capacitance compared to the rectangular shaped ventricular myocytes. Though delayed afterdepolarizations (DADs) could be evoked in a similar fraction of both cell types (80% of cells each), these led significantly more often to the occurrence of spontaneous action potentials (sAPs) in ventricular myocytes. Interestingly, numerous early afterdepolarizations (EADs) were observed in the majority of ventricular myocytes, but there was no EAD in any atrial myocyte (EADs per cell; atrial myocytes: 0±0; n=25/12 animals; ventricular myocytes: 1.5 [0 – 43]; n=20/12 animals; p<0.05). At the same time, the action potential duration to 90% decay (APD90) was unaltered and the APD50 even increased in atrial versus ventricular myocytes. However, the depolarizing L-type Ca2+ current (ICa) and Na+/Ca2+-exchanger inward current (INCX) were significantly smaller in atrial versus ventricular myocytes. Conclusions: In mice, atrial myocytes exhibit a substantially distinct occurrence of proarrhythmic afterdepolarizations compared to ventricular myocytes, since they are in a similar manner susceptible to DADs but interestingly seem to be protected against EADs and show less spontaneous action potentials. Key factors in the generation of EADs like ICa and INCX were significantly reduced in atrial versus ventricular myocytes, which may offer a mechanistic explanation for the observed protection against EADs. These findings may be of relevance for current studies on atrial level in murine models to develop targeted strategies for the treatment of atrial arrhythmia.